PRM index: an innovative tool for measuring partner relational aspects in Indian automobile sector. (1st January 2014) - Agarwal, Anuja; Singh, Deepali
This research work aims at developing a valid and authentic partner relationship management (PRM) index specific to Indian automobile industry. Review of existing literature reveals that majority of organisations have implemented PRM for building and maintaining value-laden relationship with their channel partners but no standard measure is available to evaluate how effectively PRM is being implemented and what can be the possible strategies one must formulate for utilising best benefits out of PRM practices. This study focuses on bridging this gap. Factors contributing towards PRM were identified through exhaustive review of literature followed by depth interview and questionnaire survey. A standard methodology for scale development is used followed by index development through case-based method. PRM has emerged as a multi-dimensional construct comprising factors namely, trust, collaboration, commitment, flexibility and knowledge management. The proposed index can be tested across other business and national contexts so as to judge its robustness. Effective use of PRM index will ultimately add value to the value chain of any company.